2017
DOI: 10.1103/physrevlett.118.095301
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle Approach to Molecules Interacting with Quantum Solvents

Abstract: Understanding the behavior of molecules interacting with superfluid helium represents a formidable challenge and, in general, requires approaches relying on large-scale numerical simulations. Here we demonstrate that experimental data collected over the last 20 years provide evidence that molecules immersed in superfluid helium form recently-predicted angulon quasiparticles [Phys. Rev. Lett. 114, 203001 (2015)]. Most important, casting the many-body problem in terms of angulons amounts to a drastic simplifica… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
107
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 72 publications
(115 citation statements)
references
References 106 publications
8
107
0
Order By: Relevance
“…In order to derive the simplest possible model, we take into account only the isotropic term, λ = ξ = 0, as well as the leading anisotropic term, λ = ξ = 3. It has been previously shown [22,24] that the effects of helium can be parametrized by a few characteristic properties of the molecule-helium potential, such as the PES anisotropy and the depth of its minima, which renders the fine details of the PES irrelevant. Therefore, in order to further simplify the model, we choose effective potentials characterized by the Gaussian form-factors, f λξ (r) = u λξ (2π) −3/2 e − r 2 2r 2 λξ , such that their magnitude, u λξ , and range, r λξ , reproduce known properties of the moleculehelium interaction.…”
Section: /2 Lm K0mentioning
confidence: 99%
See 3 more Smart Citations
“…In order to derive the simplest possible model, we take into account only the isotropic term, λ = ξ = 0, as well as the leading anisotropic term, λ = ξ = 3. It has been previously shown [22,24] that the effects of helium can be parametrized by a few characteristic properties of the molecule-helium potential, such as the PES anisotropy and the depth of its minima, which renders the fine details of the PES irrelevant. Therefore, in order to further simplify the model, we choose effective potentials characterized by the Gaussian form-factors, f λξ (r) = u λξ (2π) −3/2 e − r 2 2r 2 λξ , such that their magnitude, u λξ , and range, r λξ , reproduce known properties of the moleculehelium interaction.…”
Section: /2 Lm K0mentioning
confidence: 99%
“…Recently, it was predicted that a superfluid can acquire angular momentum via a different, microscopic route, which takes effect in the presence of rotating impurities, such as molecules [6][7][8][9][10][11][12][13]. In particular, it was demonstrated that a rotating impurity immersed in a superfluid forms the 'angulon' quasiparticle, which can be thought of as a rigid rotor dressed by a cloud of superfluid excitations carrying angular momentum [14-21].The angulon theory was able to describe, in good agreement with experiment, renormalization of rotational constants [22,23] and laser-induced dynamics [24,25] of molecules in superfluid helium nanodroplets. One of the key predictions of the angulon theory are the socalled 'angulon instabilities ' [14-16] that occur at some critical value of the molecule-superfluid coupling where the angulon quasiparticle becomes unstable and one or a few quanta of angular momentum are resonantly transferred from the impurity to the superfluid.…”
mentioning
confidence: 93%
See 2 more Smart Citations
“…Recently, it was shown that interaction of such orbital impurities with a many-particle environment can be rationalized by using the concept of the angulon quasiparticle [52][53][54][55][56][57][58]. While in the case of polarons the bath degrees of freedom couple to the impurity's translational motion, in angulons the orbital angular momentum is redistributed between the impurity and the many-particle environment.…”
Section: Introductionmentioning
confidence: 99%